Energy and resource use assessment of graphene as a substitute for indium tin oxide in transparent electrodes. (20th September 2016) - Arvidsson, Rickard; Kushnir, Duncan; Molander, Sverker; Sandén, Björn A.
Abstract: One of the most promising applications of graphene is as material in transparent electrodes in applications such as liquid crystal displays (LCDs) and solar cells. In this study, we assess life cycle resource requirements of producing an electrode area of graphene by chemical vapor deposition (CVD) and compare to the production of indium tin oxide (ITO). The resources considered are energy and scarce metals. The results show that graphene layers can have lower life cycle energy use than ITO layers, with 3–10 times reduction for our best case scenario. Regarding use of scarce metals, the use of indium in ITO production is more problematic than the use of copper in graphene production, although the latter may constitute a resource constraint in the very long run. The substitution of ITO by graphene thus seems favorable from a resource point of view. Higher order effects may outweigh or enhance the energy use benefit. For example, cheaper, graphene-based electrodes may spur increased production of LCDs, leading to increased absolute energy use, or spur the development of new energy technologies, such as solar cells and fuel cells. The latter could potentially lead to larger absolute reductions in resource use if these new technologies will replace fossil-based energy systems.